Corrosion of Nickel-Titanium Orthodontic Archwires in Saliva and Oral Probiotic Supplements - Ines Musa Trolić; Gianluca Turco; Luca Contardo; Nikolina Leona Serdarević; Helena Otmačić Ćurković; Stjepan Špalj (Acta Stomatologica Croatica, 2017)
Objectives: The aim of the study was to examine how probiotic supplements affect the corrosion stability of orthodontic archwires made of nickel-titanium alloy (NiTi). Materials and Methods: Ni-Ti archwires (0.508x0.508 and having the length of 2.5 cm) were tested. The archwires (composition Ni=50.4%, Ti=49.6%) were uncoated, nitrified and rhodium coated. Surface microgeometry was observed by using scanning electron microscope and surface roughness was measured by profilometer through these variables: roughness average, maximum height and maximum roughness depth. Corrosion was examined by electrochemical method of cyclic polarisation. Results: Rhodium coated alloy in saliva has significantly higher general corrosion in saliva than nitrified alloy and uncoated alloy, with large effect size (p=0.027; η2=0.700). In the presence of probiotics, the result was even more pronounced (p<0.001; η2=0.936). Probiotic supplement increases general and localised corrosion of rhodium coated archwire and slightly decreases general corrosion and increases localised corrosion in uncoated archwire , while in the case of nitrified archwire the probability of corrosion is very low. The differences in surface roughness between NiTi wires before corrosion are not significant. Exposure to saliva decreases roughness average in rhodium coated wire (p=0.015; η2=0.501). Media do not significantly influence surface microgeometry in nitrified and uncoated wires. Conclusion: Probiotic supplement affects corrosion depending on the type of coating of the NiTi archwire. It increases general corrosion of rhodium coated wire and causes localised corrosion of uncoated and rhodium coated archwire. Probiotic supplement does not have greater influence on surface roughness compared to that of saliva.